2017
DOI: 10.1016/j.proci.2016.06.133
|View full text |Cite
|
Sign up to set email alerts
|

Rate coefficients for fuel + NO2: Predictive kinetics for HONO and HNO2 formation

Abstract: High-accuracy electronic structure calculations and transition state theory are used to predict the rate coefficients for the H-abstraction reactions H 2 + NO 2 and CH 4 + NO 2. In each case, three different HNO 2 isomers are formed: cis-HONO, trans-HONO, and HNO 2. These results are used as benchmarks to test different combinations of density functionals and basis sets. The performance of these DFT methods are evaluated both with and without the use of subsequent CCSD(T)-F12a single-point energy corrections. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 45 publications
8
49
0
Order By: Relevance
“…As said by Zhang et al [37], the total rate of the 3 isomers formation calculated by Chai and Goldsmith [30] is in excellent agreement with that reported in both the Park et al [36] experimental measurement and Rasmussen et al [9] calculation. In this work, we use the recent kinetic parameters for the three different isomers from Chai and Goldsmith [30]. Although modeling studies rarely distinguish the HON O isomers as the products of R9, a slight improvement in the onset temperature of H 2 conversion at all conditions was found in this work including the different isomers.…”
Section: Kinetic Modelsupporting
confidence: 87%
See 2 more Smart Citations
“…As said by Zhang et al [37], the total rate of the 3 isomers formation calculated by Chai and Goldsmith [30] is in excellent agreement with that reported in both the Park et al [36] experimental measurement and Rasmussen et al [9] calculation. In this work, we use the recent kinetic parameters for the three different isomers from Chai and Goldsmith [30]. Although modeling studies rarely distinguish the HON O isomers as the products of R9, a slight improvement in the onset temperature of H 2 conversion at all conditions was found in this work including the different isomers.…”
Section: Kinetic Modelsupporting
confidence: 87%
“…Chai and Goldsmith [30] studied rate coefficients for fuel+N O 2 , predicting the formation of HONO, and they distinguished 3 different isomers (cis-HON O, trans-HON O and HN O 2 ). As said by Zhang et al [37], the total rate of the 3 isomers formation calculated by Chai and Goldsmith [30] is in excellent agreement with that reported in both the Park et al [36] experimental measurement and Rasmussen et al [9] calculation. In this work, we use the recent kinetic parameters for the three different isomers from Chai and Goldsmith [30].…”
Section: Kinetic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two recent directions for engine improvement, such as exhaust gas recirculation [12] and the addition of alkyl-nitrates as additives to increase reactivity [13], introduce larger concentrations of NO x in the fuel-air mixture prior to ignition. As reported by Chai and Goldsmith [14], the reaction between fuel (RH) and NO 2 : RH+NO 2 R+HONO is one reaction channel for HONO formation (Figure 1). Moreover, previous studies on the effects of NO addition during alkanes oxidation [15] reported another HONO reaction channel via NO+OH+MHONO+M at low temperatures is a key chain-terminating reaction to inhibit reactivity.…”
Section: Introductionsupporting
confidence: 53%
“…works (Chai and Goldsmith, 2017;Shrestha et al, 2018;Skreiberg et al, 2004). In 520 addition, Houshfar et al (2012) performed biomass combustion kinetic modeling with 521 reduced mechanism via sensitivity analysis.…”
mentioning
confidence: 99%